PENDEKATAN MODEL KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI PEMBELAJARAN KIMIA MAN 2 KOTA PADANG - Maywai Loza (Orbital: Jurnal Pendidikan Kimia, 2017)
The learning process requires appropriate and effective learning strategies to achieve the expected learning objectives. Compatibility of learning strategies with the condition of students greatly affect the outcomes of student learning process. STAD type cooperative model approach is considered suitable to motivate and increase student participation in chemistry learning process in grade 2 students of class X IS 2 MAN 2 Padang City. In relation to that has been done classroom research that aims to determine the application of STAD type cooperative model and LKS and concept map in the chemistry subjects cross-interest in students of class X IS 2 MAN 2 Padang City. Classroom action research is designed using STAD type cooperative model approach and LKS and concept map on chemical bonding material. The research sample class is the students of class X IS 2 MAN 2 Padang City registered in the odd semester of learning year 2017/2018 with the number of students 39 people. The study consists of two cycles and each cycle consists of four stages (planning, implementation, evaluation, and reflection), in cycle 1 is STAD and LKS and in cycle 2 is STAD and LKS and concept map. The results showed that STAD type cooperative model approach is accompanied by LKS and concept map can increase cognitive learning outcomes, positive activities and decrease negative activity in chemistry learning cross-interest in students of class X IS 2 MAN 2 Padang City.